5C.09: HERITABILITY OF RENAL FUNCTION PARAMETERS AND ELECTROLYTE LEVELS IN THE SWISS POPULATION. (June 2015) - Moulin, F.; Ponte, B.; Pruijm, M.; Ackermann, D.; Guessous, I.; Ehret, G.; Bonny, O.; Pechere-Bertschi, A.; Staessen, J. A.; Paccaud, F.; Mohaupt, M.; Martin, P.Y.; et al.
Abstract : Objective: Electrolytes handling by the kidney is essential for volume and blood pressure (BP) homeostasis but their distribution and heritability are not well described. We estimated the heritability of kidney function as well as of serum and urine concentrations, renal clearances and fractional excretions for sodium, chloride, potassium, calcium, phosphate and magnesium in a Swiss population-based study. Design and method: Nuclear families were randomly selected from the general population in Switzerland. We estimated glomerular filtration rate (eGFR) using the CKD-EPI and MDRD equations. Urine was collected separately during day and night over 24-hour. We used the ASSOC program (S.A.G.E.) to estimate narrow sense heritability, including as covariates in the model: age, sex, body mass index and study center. Results: The 1128 participants (537 men and 591 women from 273 families), had mean (sd) age of 47.4(17.5) years, body mass index of 25.0 (4.5) kg/m2 and CKD-EPI of 98.0(18.5) mL/min/1.73 m2. Heritability estimates (SE) were 46.0% (0.06), 48.0% (0.06) and 18.0% (0.06) for CKD-EPI, MDRD and 24-hour creatinine clearance (P < 0.05), respectively. Heritability [SE] of serum concentration was highest for calcium (37%[0.06]) and lowest for sodium (13%[0.05]). Heritabilities [SE] of 24-h urine concentrations and excretions, and of fractional excretions were highest for calcium (51%[0.06], 44%[0.06] and 51%[0.06], respectively) and lowest for potassium (11%[0.05], 10%[0.05] and 16%[0.06], respectively). All results were statistically different from zero. Figure. No caption available. Conclusions: Serum and urine levels, urinary excretions and renal handling of electrolytes, particularly calcium, are heritable in the general adult population. Identifying genetic variants involved in electrolytes homeostasis may provide useful insight into the pathophysiological mechanisms involved in common chronic diseases such as kidney diseases, hypertension and diabetes.